O´Neill: a collection of critical essays - Gassner, John 1903-1967 (Twentieth Century Views)
One's outer life passes in a solitude haunted by the masks of others; one´s inner life passes in a solitude haunted by the masks of oneself." Thus even offstage Eugene O'Neill chose the theatrical metaphor of "masks" to express his dark conception of the human predicament. For the theater shaped and dominated O'Neill, just as he carne to shape and domínate the theater. In this collection of criticism, John Gassner, eminent theater historian, has set drama critics, scholars, and theater professionals to the task of assessing O´Neill both as creature and creator of the American tneater. Whether they evalúate the effects of O'Neill's tortured family background on his work or analyze his brooding dramas, these essays reflect the efforts of O'Neill's admirers ?and detráctors to define the elusive forcé that inspires his plays.